Molecular and genomic characterisation of cryptic chromosomal alterations leading to paternal duplication of the 11p15.5 Beckwith-Wiedemann region. Issue 8 (1st August 2006) - Russo, S; Finelli, P; Recalcati, M P; Ferraiuolo, S; Cogliati, F; Dalla Bernardina, B; Tibiletti, M G; Agosti, M; Sala, M; Bonati, M T; Larizza, L
Abstract : Background: Beckwith-Wiedemann syndrome (BWS) is an overgrowth disorder with increased risk of paediatric tumours. The aetiology involves epigenetic and genetic alterations affecting the 11p15 region, methylation of the differentially methylated DMR2 region being the most common defect, while less frequent aetiologies include mosaic paternal 11p uniparental disomy (11patUPD), maternally inherited mutations of the CDKN1C gene, and hypermethylation of DMR1. A few patients have cytogenetic abnormalities involving 11p15.5. Methods: Screening of 70 trios of BWS probands for 11p mosaic paternal UPD and for cryptic cytogenetic rearrangements using microsatellite segregation analysis identified a profile compatible with paternal 11p15 duplication in two patients. Results: Fluorescence in situ hybridisation analysis revealed in one case the unbalanced translocation der(21)t(11;21)(p15.4;q22.3) originated from missegregation of a cryptic paternal balanced translocation. The second patient, trisomic for D11S1318, carried a small de novo dup(11)(p15.5p15.5), resulting from unequal recombination at paternal meiosis I. The duplicated region involves only IC1 and spares IC2/LIT1, as shown by fluorescent in situ hybridisation (FISH) mapping of the proximal duplication breakpoint within the amino-terminal part of KvLQT1. Conclusions: An additional patient with Wolf-Hirschorn syndrome was shown by FISH studies to carry a der(4)t(4;11)(p16.3;p15.4), contributed by a balanced translocation father. Interestingly, refined breakpoint mapping on 11p and the critical regions on the partner 21q and 4p chromosomal regions suggested that both translocations affecting 11p15.4 are mediated by segmental duplications. These findings of chromosomal rearrangements affecting 11p15.5–15.4 provide a tool to further dissect the genomics of the BWS region and the pathogenesis of this imprinting disorder.